The loyalty journey of BBA and MBA alumni in Indonesia: a strategic alumni marketing perspective - Liza Agustina Maureen Nelloh; Liza Agustina Maureen Nelloh; Hartoyo Hartoyo; Ujang Sumarwan; Aman Wirakartakusumah (Frontiers in Communication)
Alumni loyalty reflects the long-term educational impact and plays a strategic marketing role in supporting institutional branding and sustainability. However, despite its importance, limited study explores the comprehensive alumni loyalty journey, particularly on how the educational experience translates into post-graduate loyalty, and how this differs across program levels such as Bachelor of Business Administration (BBA) and Master of Business Administration (MBA). This study investigates strategic alumni marketing perspective of Higher Education Service Quality (HEISQUAL), experience value, alumni satisfaction, and relationship quality in influencing loyalty. Employing Partial Least Square—Structural Equation Modeling (PLS-SEM) with Multi-Group Analysis (MGA), the study surveyed 201 alumni from a leading Indonesian business school. Results show that HEISQUAL significantly influences experience value and satisfaction but not to relationship quality. Experience value strongly affects both satisfaction and relationship quality, while only relationship quality directly drives alumni loyalty. Additionally, MBA alumni exhibit higher loyalty than BBA alumni. Although limited to a single business school, this study contributes to relationship marketing literature and emphasizing the importance of alumni as the brand advocates for business schools, especially through continuous communication strategies, such as recognizing loyal alumni through personalized appreciation programs and public acknowledgment initiatives.